Enterprise social media in contemporary workplaces: a computational literature review - Zhou, Siyu; Yin, Jiarui (Frontiers in Communication, 2025)
Enterprise social media (ESM)—digital platforms that support internal communication, collaboration, and knowledge sharing—have revolutionized contemporary workplaces, particularly amid the growing prevalence of hybrid and remote work. Despite their growing significance, questions persist regarding the impacts of ESM on organizations and the conditions necessary for their effective implementation and management. To address this gap, we conducted a computational literature review of 320 peer-reviewed articles published from 2013 to 2024, utilizing the Latent Dirichlet Allocation (LDA) topic modeling algorithm to provide a comprehensive survey of ESM research. Our analysis pinpoints three central themes: ESM enactment process, micro-level impacts (e.g., job performance), and macro-level outcomes (e.g., strategic knowledge management). We also observe increasing scholarly attention to emerging ESM-mediated behaviors, digital competence, and the interplay between ESM and public social media. We propose an integrative framework that positions ESM enactment as a dynamic, multi-level process and outline a research agenda for future inquiry. By consolidating a decade of scholarship, this review provides timely insights and guidance for advancing theoretical understanding and effective use of ESM in today’s digital workplaces.